Functional Antimicrobial Surface Coatings Deposited onto Nanostructured 316L Food-Grade Stainless Steel - A. Silvia González; Angela Riego; Victor Vega; Javier García; Serena Galié; Ignacio Gutiérrez del Río; Maria del Valle Martínez de Yuso; Claudio Jesús Villar; Felipe Lombó; Victor Manuel De la Prida (Nanomaterials, 2021)
In our study, we demonstrated the performance of antimicrobial coatings on properly functionalized and nanostructured 316L food-grade stainless steel pipelines. For the fabrication of these functional coatings, we employed facile and low-cost electrochemical techniques and surface modification processes. The development of a nanoporous structure on the 316L stainless steel surface was performed by following an electropolishing process in an electrolytic bath, at a constant anodic voltage of 40 V for 10 min, while the temperature was maintained between 0 and 10 °C. Subsequently, we incorporated on this nanostructure additional coatings with antimicrobial and bactericide properties, such as Ag nanoparticles, Ag films, or TiO2 thin layers. These functional coatings were grown on the nanostructured substrate by following electroless process, electrochemical deposition, and atomic layer deposition (ALD) techniques. Then, we analyzed the antimicrobial efficiency of these functionalized materials against different biofilms types (Candida parapsilosis, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus epidermidis). The results of the present study demonstrate that the nanostructuring and surface functionalization processes constitute a promising route to fabricate novel functional materials exhibiting highly efficient antimicrobial features. In fact, we have shown that our use of an appropriated association of TiO2 layer and Ag nanoparticle coatings over the nanostructured 316L stainless steel exhibited an excellent antimicrobial behavior for all biofilms examined.